Analisis Faktor Penyebab Rendahnya Minat Masyarakat Memilih Produk Pembiayaan Pada Bank Syariah - Endah Nur Rahmawati; Nur Kafid; Taufiq Wijaya (Institut Ilmu Keislaman Annuqayah, 2017)
Since 1992 Graphic development of Syaria Bank in Indonesia continues to increase. The increasing number of branches of Syaria Banks in all regions is an indicator. But if viewed from the type of financing offered by Syaria Bank, the public interest especially the Muslim community to use it is low compared to conventional banks. People in the Islamic Higher Education environment, which became the focus of this research were more likely to use financial products in conventional Banks than Syaria Banks. There are several factors that cause the low public interest, such as environment, cost, product, process, competitors, personal trait (People), promotion, margin, Individual interests. From the results of the Confirmatory Factor Analysis test data indicate that each indicator or the forming dimension of each latent variable shows good and in a unified dimension. That is, all these factors really affect the people’s decision not to choose the financinal products offered by Syaria Bank in Indonesia.